Garbage - Ganeri, Anita, 1961- (New York, NY : DK/Penguin Random House, 2021)
Explains waste management problems humans have encountered throught history and how we deal with it now, highlighting key global concerns related to garbage disposal, such as space waste, the problem of plastic, and growing landfills.
Includes index.
6.3
3-6.
3-6
Keywords: Pollution prevention -- Juvenile literature; Refuse and refuse disposal -- Juvenile literature; Waste minimization -- Juvenile literature; Pollution prevention; Refuse and refuse disposal; Waste minimization; Pollution -- Prevention; Refuse and refuse disposal